1298. Population Pharmacokinetics of Ceftazidime-avibactam among Critically-ill Patients with and without Receipt of Continuous Renal Replacement Therapy. (31st December 2020) - Kline, Ellen G; Nguyen, Minh Hong T; McCreary, Erin K; Wildfeuer, Brett; Kohl, Josh; Hughes, Kailey L; Jones, Chelsea E; Doi, Yohei; Doi, Yohei; Shields, Ryan K
Abstract: Background: Ceftazidime-avibactam (CAZ-AVI) is used to treat multidrug-resistant infections. There are limited pharmacokinetic (PK) data among critically-ill patients (pts) and no dosing recommendations for those receiving continuous renal replacement therapy (CRRT). Methods: We conducted a PK study of CAZ-AVI among pts with and without CRRT. Serial blood samples were collected at 0 (pre-dose), 2, 4, 6, and 8 hours after CAZ-AVI administration. All doses were infused over 2h. Samples were centrifuged and plasma stored at -80°C until analysis by a Shimadzu Nexera XD UHPLC with a Shimadzu 8045 MS. Transitions were monitored in positive mode for CAZ ( m/z 274.05 < 80.05) and negative mode for AVI (264.00 < 95.90). The assay was reproducible and linear over a range of 0.1 – 20 µg/mL for AVI and 1 – 200 µg/mL for CAZ. non-compartmental analyses were used. Results: 96 plasma samples from 20 pts were included in the study. Median age was 56 years (range: 31 – 74), 55% were male, and 90% were in the ICU at the time of collection. CZA dosing regimens included 2.5g IV q 8h (n=15), 1.25g IV q 8h (n=2), 0.94g IV q 24h (n=1), and 0.94g IV q 48h (n=2). 7 pts received CRRT (median blood and dialysate flow rates were 250 mL/min and 2.5 L/h, respectively; 86% received 2.5g IV q 8h) and 2 pts received intermittent hemodialysis (iHD). Among remaining pts, median creatinine clearance (CrCl) by Cockcroft-Gault was 91ml/min (range: 37 – 168 ml/min). PK values for CAZ and AVI are shown in the Table. Individual concentration-time profiles for patients receiving 2.5g IV q 8h are shown in the Figure. For patients receiving 2.5g IV q8h, CAZ and AVI median (IQR) AUCs were 525.6 hr*µg/ml (403.2, 762.0) and 83.7 (57.3, 129.5), respectively. For those on CRRT receiving the same dose, CAZ and AVI median (IQR) AUCs were 450.2 (450.0, 558.4) and 102.4 (100.7, 142.3), respectively. CAZ pharmacodynamics (PD) targets of 100% f T > 1x and 4x MIC were achieved in 90% and 55% of pts, respectively. AVI PD targets of 100% f T > 1 and 2.5µg/mL were achieved in 100% and 80% of pts, respectively. Treatment-emergent adverse events were not reported in any case. Ceftazidime and avibactam pharmacokinetic parameters among critically-ill patients Conclusion: Among this cohort of critically-ill pts, CAZ and AVI exposures varied; however, most pts achieved PD targeted exposures, including those patients receiving CRRT and a standard dosing regimen of 2.5g IV q 8h. Disclosures: Erin K. McCreary, PharmD, Entasis (Advisor or Review Panel member)Summit (Advisor or Review Panel member) Ryan K. Shields, PharmD, MS, Allergan (Advisor or Review Panel member, Research Grant or Support)Entasis (Advisor or Review Panel member)Melinta (Research Grant or Support)Menarini (Consultant)Merck (Advisor or Review Panel member, Research Grant or Support)Shionogi (Advisor or Review Panel member, Research Grant or Support)Summit (Advisor or Review Panel member)Tetraphase (Research Grant or Support)Venatorx (Advisor or Review Panel member, Research Grant or Support)